Analysis of Evaluation Models in Physical Education Learning: Systematic Literature review - Hasyim, Andi Hasriadi; Haris, Iyan Nurdiyan; Yulianto, Ari Gana (Universitas Majalengka, 2024)
Knowledge about evaluation has an important role in overcoming various problems in physical education learning. There are various types of program evaluation models used, and therefore, the aim of this research is to explore and review the application of various program evaluation models that have been carried out in the context of physical education learning. The method used in this research is a literature review. Data was collected from three database sources, namely Google Scholar, Garuda Ristekdikti, and Sinta Journal, using the keywords